Disability Justice: Decentering Colonial Knowledge, Centering Decolonial Epistemologies - Allen, Alexandra; Penketh, Claire; Wexler, Alice (Research in Arts and Education, 2022)
This thematic issue of Research in Arts and Education derives from the presentations and keynote addresses of the 3rd International Disability Studies, Arts & Education Conference (DSAE). In light of the ongoing global pandemic, the conference was held online for the ﬁrst time from October 7 to October 9, 2021. In preparation for the conference, we recognized how the pandemic had fore-fronted social justice in disability studies, art education, and society: the inequity of economic resources, the exploitation of the most vulnerable people, systemic racism, and the disproportionate effects of climate change on non-industrial countries. The intersection of racial, able-bodied, ethnic, sexual, cultural, gendered, environmental, and economic power disparities are interlocking oppressions that cannot be detached from colonial history. Decolonial work is foregrounded in the lived realities of marginalized people who diverge from neurotypical and dominant systems. Thus, these issues were threaded throughout the conference presentations.